Sexual Dimorphism and Body Reconstruction of a Hornless Rhinocerotid, Plesiaceratherium gracile, From the Early Miocene of the Shanwang Basin, Shandong, China - Lu, Xiaokang; Deng, Tao; Zheng, Xiaoting; Li, Fuchang (Frontiers in Ecology and Evolution, 2020)
Based on the numerous new specimens of Plesiaceratherium gracile from the Early Miocene Shanwang Basin, China, we investigated the sexual dimorphism and reconstructed the body. The sexual dimorphism of P. gracile is the size of both the lower incisor i2 (length male/female ratio = 2.69, width M/F = 1.63) and the upper incisor I1 (length M/F = 1.63). Other mensural variations show their ranges greatly overlapping on both genders, with a lower M/F ratio, they hence can not be interpreted as sexual dimorphism. The large-sized body, the strong sexual difference of incisors, and the minor population gap between both gender (male/female = 29/21) suggest that P. gracile is polygynous and has a solitary life style. On the other hand, we reconstruct the body of P. gracile. The head-body length is 2796–3117 mm, the shoulder height is 1476–1627 mm, and the body weight is about 1198 kg. All skeletons have the ventral edge of the thorax flushing with the olecranon of the ulna. Meanwhile, the spinous processes of the posterior thoracic vertebrae and the lumbar vertebrae are always vertical, the metatarsal-femur ratio and the tibia-femur ratio are higher, and the two joint angles between the scapula, the humerus, and the radius are 102°–143° and 115°–160°, respectively, which indicates that P. gracile has a mediportal limb and a horse-gallop running type. Furthermore, the limb-segments comparisons of P. gracile and other rhinos demonstrate that the proximal long bones, including the scapula, the humerus and the femur, are important for the body height whatever their body is large-sized or small-sized; the distal parts of the limb, including the metacarpus and the metatarsus, are sensitive to the body mass changes.